Portable telepathology: methods and tools - Roca Ma José; Alfaro Luis (BMC, 2008)
Abstract Telepathology is becoming easier to implement in most pathology departments. In fact e-mail image transmit can be done from almost any pathologist as a simplistic telepathology system. We tried to develop a way to improve capabilities of communication among pathologists with the idea that the system should be affordable for everybody. We took the premise that any pathology department would have microscopes and computers with Internet connection, and selected a few elements to convert them into a telepathology station. Needs were reduced to a camera to collect images, a universal microscope adapter for the camera, a device to connect the camera to the computer, and a software for the remote image transmit. We found out a microscope adapter (MaxView Plus) that allowed us connect almost any domestic digital camera to any microscope. The video out signal from the camera was sent to the computer through an Aver Media USB connector. At last, we selected a group of portable applications that were assembled into a USB memory device. Portable applications are computer programs that can be carried generally on USB flash drives, but also in any other portable device, and used on any (Windows) computer without installation. Besides when unplugging the device, none of personal data is left behind. We selected open-source applications, and based the pathology image transmission to VLC Media Player due to its functionality as streaming server, portability and ease of use and configuration. Audio transmission was usually done through normal phone lines. We also employed alternative videoconferencing software, SightSpeed for bi-directional image transmission from microscopes, and conventional cameras allowing visual communication and also image transmit from gross pathology specimens. All these elements allowed us to install and use a telepathology system in a few minutes, fully prepared for real time image broadcast.